(untitled) (Damascus University Journal for legal sciences, 2025)
Lawsuit is the legal means that enables individuals to obtain their right through the judiciary. However, the civil lawsuit may be obstructed by one of the symptoms that lead to the interruption of the litigation. The jurisprudence in Syria has flopped regarding the impact of the minor’s puberty on the progress of the civil lawsuit and the consequent interruption of the litigation. Minor’s puberty during the lawsuit does not result in the interruption of the litigation if the minor does not raise any objection, as it results in turning the legal representation into a representation by agreement, unless he objects to the guardian’s representation leading to the interruption of all procedures that took place after the puberty without affecting the origin of the right.